Water management in the Western Mediterranean basin: An archaeological approach (II) - Buxó R. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
This paper presents an approach to different aspects related to water management of the prehistoric societies in the Iberian Peninsula. It tries to evaluate and assess the water needs and the potentially exploitable water resources in prehistoric times: uses of water, drainage and water infrastructures, industrial water uses and water use in agriculture. The results provide a deeper knowledge of water management through analyses of the architectural and functional infrastructure designed to solve the problem of water supply and drainage. Water supply sources can be categorized in three main groups: underground water and springs, water courses and masses of accumulated water. Furthermore, the paper discusses archaeological evidence of water management from prehistoric times in the south-eastern Iberian Peninsula. The societies in that area already then had channelled water and probably had irrigation systems that channelled water from galleries cut into the rock to the cultivated crops. This is a sign of a true culture of water that has remained constant from the prehistory to the Hispano-Islamic culture and to the present day.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)